Peta Pemikiran Keagamaan Islam di Indonesia; Dampak Positif dan Negatif bagi Umat - Musthofa Musthofa (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2015)
Judging by the more fundamental in the religious thought of Islam in Indonesia is multi dimensial that will get some variants ratio of absolute thought. It is actually not a paradigm, because in the social sciences there must be various paradigms, not mutually exclusive, but rather mutually clump together, although there are three forms of social thought of Islam, which is called by wearing their own terms, as